Patients’ expectations of ‘first-contact care’ consultations with nurse and general practitioners in primary care - Redsell, Sarah; Jackson, Clare; Stokes, Tim; Hastings, Adrian; Baker, Richard (Radcliffe Publishing, 2007)
Background Patients’ attending UK primary care currently receive first-contact care services from nurses as well as general practitioners (GPs). Although randomised trials have reported higher satisfaction following nurse consultations,the relationship between patients’ prior expectations and satisfaction for nurse consultations has not been fully explored. Objective To explore patients’ expectations of their consultations with nurses or GPs,whether or not they are met,and their overall satisfaction. Methods Participants were adults attending general practice for same-day first-contact care consultations during 2004. Qualitative data were collected prior to and up to two weeks after the consultation. Semi-structured interview and constant comparative methods were used in order to explore the issue from the perspective of the participants. The main themes that emerged from this data set have been reported elsewhere. This paper reports on further analysis of participants’ expectations from the first interviews,w ith whether or not these were met from the second interviews. Results Twenty-eight participants were interviewed prior to their consultation,and 19 of these participants were interviewed subsequently. Eighteen paired interviews with either a GP (n = 10) or nurse (n = 8) were used for the analysis. Although participants wanted certainty with regard to the outcome of their consultation,most found it difficult to articulate all their expectations of either the nurse or GP. Participants knew what to expect from their usual GP,and were generally satisfied with the outcome. They had little experience of nurse-led consultations and lower expectations of them. Retrospectively,most participants were satisfied with their nurse-led consultation. Conclusion The skills,know ledge and authority of nurses undertaking first-contact care were not fully understood by participants,and they may adjust their expectations to take account of this. Patients consulting with nurses may report higher satisfaction rates with nurses because they have fewer expectations beforehand,and if these are exceeded in the resulting consultation,their satisfaction is, accordingly,greater.